Mergers, Acquisitions and Banking Consolidation in Central and Eastern Europe - Andreea Nicoleta Popovici (CES Working Papers, 2013)
Acquisitions and mergers are the growth and expansion strategies that are commonly used by the companies in all over the world because of several reasons such as increasing the profit, sales and market share, entering into new markets, operating with economics of scale, coping with managerial problems and so on. This article underlines the characteristics of mergers and acquisitions (M&A), the different types of M&A, the challenges and opportunities for the banking system in Central and Eastern Europe and we analyze the implications of the recently observed sharp expansion of foreign banks in the Central and Eastern European Countries.
Keywords: G21; G30; G34; 330; banks; M&A; Central and Eastern Europe; foreign Romania